Congestive heart failure. Correlation between functional class and systolic and diastolic functions assessed by Doppler echocardiography - Kamel,Cesar Selem (2001)
OBJECTIVE: To evaluate the influence of systolic or diastolic dysfunction, or both on congestive heart failure functional class. METHODS: Thirty-six consecutive patients with a clinical diagnosis of congestive heart failure with sinus rhythm, who were seen between September and November of 1998 answered an adapted questionnaire about tolerance to physical activity for the determination of NYHA functional class. The patients were studied with transthoracic Doppler echocardiography. Two groups were compared: group 1 (19 patients in functional classes I and II) and group 2 (17 patients in functional classes III and IV). RESULTS: The average ejection fraction was significantly higher in group 1 (44.84%±8.04% vs. 32.59%±11.48% with p=0.0007). The mean ratio of the initial/final maximum diastolic filling velocity (E/A) of the left ventricle was significantly smaller in group 1 (1.07±0.72 vs. 1.98±1.49 with p=0.03). The average maximum systolic pulmonary venous velocity (S) was significantly higher in group 1 (53.53cm/s ± 12.02cm/s vs. 43.41cm/s ± 13.55cm/s with p=0.02). The mean ratio of maximum systolic/diastolic pulmonary venous velocity was significantly higher in group 1 (1.52±0.48 vs. 1.08±0.48 with p=0.01). A predominance of pseudo-normal and restrictive diastolic patterns existed in group 2 (58.83% in group 2 vs. 21.06% in group 1 with p=0.03). CONCLUSION: Both the systolic dysfunction index and the patterns of diastolic dysfunction evaluated by Doppler echocardiography worsened with the evolution of congestive heart failure.